INTERMEDIAL VECTOR IN THE CREATIVE SEARCH OF CONTEMPORARY TURKISH COMPOSERS - Kupina, Daryna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of the study. The article addresses a documented gap in Ukrainian musicology by foregrounding contemporary Turkish art music as an autonomous field of artistic thinking shaped at the intersection of makam modality, usûl metrorythm, microtonality, and European compositional techniques. It approaches this repertoire through intermedial discourse, with a special focus on musical ekphrasis as a non-illustrative, intersemiotic mode of translation. The main objective of the study is to delineate the pathways of intermedial translation by which visual images are recast into the musical works of 21st century Turkish composers as projections of an alternative worldview. The theoretical foundation draws on studies S. Bruhn, L. Goehr, O. Hilewicz, А. Krawiec, among others, which delineate the methodological horizons of intermediality and intersemiotic translation. The methodology combines intermedial and holistic approaches with contextual and parameter-based analysis (modal/metrical organization, timbral-textural morphology, and sonorous processes) in order to specify the channels of transmedial transfer. The main results and conclusions. It has been proven that academic music of Turkey in the 21st century is formed at the intersection of several cultural traditions; however, its conceptual foundation is defined not so much by the assimilation of European models as by a worldview rooted in the makam system, the rhythmic organization of usul, and the ornamental continuity of the melodic line. In this cultural context, intermediality emerges as a key mechanism of reinterpretation: it enables the transformation of architectural, poetic, and plastic images into musical parameters of time, timbre, and texture, thus opening for the listener new horizons of the Eastern sonic reality. Musical ekphrasis is understood here as an intersemiotic translation of a visual “text” into a sonic syntax that preserves or structurally reconfigures the compositional and/or syntactic invariants of the source. Against this backdrop, Türkmen’s Hat exemplifies an endogenous, structurally modelled ekphrasis: the calligraphic paradigm of the line is transformed into a monophonic, continuous trajectory articulated by makam gravitations and a characteristic metric pulse; unison isophony, timbral “thickening” of single tones, microchromatic inflection, and heterophonic layering operate as acoustic analogues of the calligraphic stroke, with form conceived as the “motion of the line” rather than a pre-fabricated architecture. By contrast, Özbayrak’s The Monk by the Sea realizes an exogenous, sonorous type of ekphrasis: Friedrich’s horizon is recoded as a pedal monotone (drone), the painting’s “air” as an aeroacoustic sonority; microtonal inflections, controlled vibrato, and spectral friction shape a “wave dramaturgy,” while onomatopoeic figures (seagull cries) and contrabass sfz cues create an intermedial “double exposure” with a localized soundscape. Together, these cases articulate two operative principles of transmedialization - structural modelling and environmental sonorous modelling - thus extending the analytical apparatus for musical ekphrasis and enabling non-European repertoires to be discussed without recourse to reductive notions of illustrative program. At the same time, the study helps to remedy the documentation deficit surrounding Turkish materials by introducing two representative case studies and demonstrating how local Eastern intonational codes and European iconic images co-operate within current compositional practice.